2020
DOI: 10.1177/0268355520955083
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in the era of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) does not only affect the respiratory system but appears to be a systemic disease. Venous thromboembolism is a common manifestation in hospitalized patients with COVID-19 with a reported incidence that is significantly higher compared to other acute viral infections. The pathophysiology mechanisms have not been fully explored and autopsy studies might enhance our understanding on this topic. Microthrombi formation occurs mainly in the pulmonary vasculature but can also occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 63 publications
(144 reference statements)
2
21
0
Order By: Relevance
“…Similar observation was reported by others, that D-dimer and rising D-dimer linked to mortality [31]. The observed elevation of D-dimer might be due to direct viral-related endothelial injury [35] and other known thrombosis risk factors [36][37][38]. Additionally, the D-dimer elevation can be seen in some patients due to sepsis-induced coagulopathy [39].…”
Section: Discussionsupporting
confidence: 85%
“…Similar observation was reported by others, that D-dimer and rising D-dimer linked to mortality [31]. The observed elevation of D-dimer might be due to direct viral-related endothelial injury [35] and other known thrombosis risk factors [36][37][38]. Additionally, the D-dimer elevation can be seen in some patients due to sepsis-induced coagulopathy [39].…”
Section: Discussionsupporting
confidence: 85%
“…Besides, respiratory physiology is altered in patients with obesity, resulting in decreased functional residual capacity and expiratory reserve volume, leading to subsequent ventilation−perfusion abnormalities and hypoxaemia [ 86 , 87 ]. In addition, obesity has been associated with a high risk of developing venous thromboembolism [ 88 ], which is frequently reported in COVID-19 cases and is correlated with a poor prognosis [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several theories have suggested that PE seen in COVID‐19 correspond to microthrombus of small‐caliber pulmonary arteries, and not always from an embolic origin in extremity veins. 4 …”
Section: Discussionmentioning
confidence: 99%
“…Since it was first described, it has been linked to an increased incidence of venous thromboembolism (VTE), along with hemostatic abnormalities. 1 , 2 This has been suggested to be caused by inflammation, platelet activation, endothelial dysfunction, and other factors 3 , 4 that occur in COVID‐19 patients.…”
mentioning
confidence: 99%